Uncovering the Factors that Caused the Decline in the Civil Liberties Space on the Quality of Democracy in 2021 - Ariyan, Said; Agustin, Elsa (MID Publisher International, 2025)
The Democracy Index, compiled by the Economist Intelligence Unit (EIU), has been measuring democratic conditions across 167 countries since 2006. In 2021, Indonesia received a composite score of 6.71, placing it at rank 52 in the 'flawed democracy' category. While the electoral process and pluralism indicator scored 9.17, civil liberties remained notably low at 6.18. This study aims to identify the factors contributing to the decline in civil liberties space and its impact on the quality of democracy in Indonesia in 2021. Employing a qualitative approach through literature study, participatory observation, and interviews with political elites, academics, and civil society representatives, this research analyzes civil liberties across four dimensions: freedom of assembly and association, freedom of opinion, freedom of belief, and freedom from discrimination. The findings reveal that the decline in civil liberties is driven by restrictive regulations such as the CSO Law and the ITE Law, excessive use of force against protesters, criminalization of public expression, persistent religious intolerance, and inadequate enforcement of anti-discrimination laws. The study concludes that strengthening civil liberties requires comprehensive legal reform, enhanced human rights education for law enforcement, and genuine government commitment to protecting fundamental freedoms as pillars of democratic governance.